2D and 3D anticancer properties of C2-functionalised glucosamine-Pt (IV) prodrugs based on cisplatin scaffold - Moynihan, Eoin; Galiana-Cameo, Maria; Sandri, Monica; Ruffini, Andrea; Panseri, Silvia; Velasco-Torrijos, Trinidad; Montesi, Monica; Montagner, Diego (Frontiers in Chemistry, 2024)
A series of C2-functionalied Pt (IV) glycoconjugates based on glucosamine have been synthesised, characterised and tested as anticancer agents on a series of different 2D and 3D cancer cell lines. The carbohydrate will act as a targeted delivery system to improve the selectivity, exploiting the Warburg Effect and the GLUTs receptors that are overexpressed in most of the cancer cells. The hydroxyl at C2 of the carbohydrates does not participate in hydrogen bonding with the GLUTs receptors, making C2 an attractive position for drug conjugation as seen in literature. In this study, we use the amino functionality at the C2 position in glucosamine and Copper-catalysed Azide-Alkyne Cycloaddition “click” (CuAAC) reaction to connect the prodrug Pt (IV) scaffold to the carbohydrate. We have investigated complexes with different linker lengths, as well as acetyl protected and free derivatives. To the best of our knowledge, this study represents the first series of Pt (IV) glucosamine-conjugates functionalised at C2.